Factors Influencing the Development and Severity of Cognitive Decline in Patients with Chronic Heart Failure - Marius Militaru; Daniel Florin Lighezan; Cristina Tudoran; Mariana Tudoran; Anda Gabriela Militaru (Medicina)
Background and Objectives: Considering the increasing prevalence of chronic heart failure (CHF) and cognitive decline (CD) observed in recent decades and the complex interrelation between these two pathologies often encountered in the same patient, in this study, we aimed to highlight the connection between CHF, defined as recommended by the European Society of Cardiology guidelines, and CD, evaluated by employing five neuropsychological scales. Materials and Methods: Our study was conducted on 190 patients with very high cardiovascular risk profiles admitted between 5 September 2021 and 15 November 2023 in the Municipal Emergency Hospital Timisoara. Of these, 103 had CHF (group A) and 87 did not (group B). Results: Although similar concerning age, sex distribution, and risk factors (excepting lipid profile), patients from group A had lower Mini Mental State Evaluation (MMSE) and Montreal Cognitive Assessment (MoCA levels (p = 0.003, respectively, p = 0.017) scores, more reduced daily activity (p = 0.021), and more severe depression (p = 0.015) compared to group B. We documented statistically significant correlations between left-ventricular ejection fraction (LVEF) and the levels of N-terminal pro–B-type natriuretic peptide (NT-pro-BNP), as well as with the results of MMSE (r = 0.226, p = 0.002 and r = −0.275, p = 0.005, respectively), daily activity, and depression (p ˂ 0.001). Multi-logistic regression models indicated age, blood pressure values, decreased daily activity, and depression as risk factors for CD in patients with CHF. Conclusions: In patients with CHF, there is an increased propensity of CD, with a direct relationship between MMSE and LVEF levels and an indirect one between MMSE and NT-pro-BNP levels. The concomitance of depression and reduced activity levels are aggravating CD in these patients.